Analisis Kepuasan Pasien terhadap Pelayanan Kesehatan Menggunakan Metode Servqual Studi Kasus di Fasilitas Kesehatan Tingkat Pertama (FKTP) Klinik Universitas Brawijaya - Ulfa, Dina Maria; Arief Noviarakhman Zagladi (IPM2KPE, 2026)
This study aims to analyze the level of patient satisfaction with healthcare services by comparing patient expectations and perceptions and identifying gaps in service quality at the Primary Health Facility (FKTP) of the Brawijaya University Clinic using the SERVQUAL method. The research method used was descriptive quantitative research with a convenience sampling technique. The study sample consisted of 98 respondents, patients of the Brawijaya University Clinic, determined using the Slovin formula from a population of 4,329 patients. Data collection was conducted through a questionnaire based on the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis was performed using the SERVQUAL method to measure the gap between patient perceptions and expectations and the Wilcoxon Signed-Rank Test to determine the significance of the difference between the two. The results showed that the Tangibles dimension had a positive gap value of 0.23, indicating that the clinic's physical facilities met or even exceeded patient expectations. Meanwhile, the dimensions of Empathy (-0.27), Assurance (-0.25), Reliability (-0.22), and Responsiveness (-0.01) had negative gap values, indicating that there are still service aspects that need improvement. The Wilcoxon test results showed an Asymp. Sig. (2-tailed) value of 0.229 (>0.05), indicating no significant difference between patient expectations and perceptions of the quality of service provided. The conclusion of this study indicates that, in general, the quality of service at the Brawijaya University Clinic has met patient expectations. However, continuous improvement needs to be focused on the Empathy and Assurance dimensions to optimally enhance patient satisfaction and quality of healthcare services. Keywords: Patient Satisfaction, Service Quality, Primary Healthcare Facilities